Relationship between Quality of Student Practice and Success of Community Midwifery Practice - Nurfurqoni, Fuadah Ashri (SOSIOHUMANIKA, 2014)
ABSTRACT: Results of the study on community midwifery practice acquired several factors causing dissatisfaction. This dissatisfaction could be due to the poor quality of practice performed by students. This condition will affect the success of a community midwifery practices implemented. Thus, research needs to identify the dimensions of quality practices that may increase the success of midwifery practice community. This analytical research using cross sectional method by using stratified random sampling, conducted in April to May 2013 to 92 pregnant women and mothers of infant/toddlers who participated in the counseling and health screenings by students at community midwifery practice. Variable on the quality of student practice and benefits practices were measured using questionnaires. The statistical test used were the Pearson Test, the Multiple Linear Regression Test, and the most influential factor analyzed using path analysis. The results show that quality of student practice related to success of community midwifery practice (r = 0.616, p < 0.001). The most influential dimensions of quality that is empathy, assurance, and subject age as a confounding variable (p value < 0.001); and effect of combined was 33.7% (p < 0.001). Finally, the quality of student practices associated with successful community midwifery practice, the most influential dimensions are empathy and assurance.KEY WORD: Quality, service, community, midwifery, practices, dissatisfaction, students, counseling and health screening, empathy, and assurance.Â RESUME: âHubungan antara Kualitas Praktek Mahasiswa dengan Keberhasilan Praktek Kebidanan Komunitasâ. Hasil penelitian pada praktek kebidanan komunitas mengakuisisi beberapa faktor penyebab ketidakpuasan. Ketidakpuasan ini bisa disebabkan oleh buruknya kualitas praktek yang dilakukan oleh mahasiswa. Kondisi ini akan mempengaruhi keberhasilan suatu praktek kebidanan komunitas ketika dilaksanakan. Dengan demikian, penelitian perlu mengidentifikasi dimensi praktek berkualitas yang dapat meningkatkan keberhasilan komunitas praktek kebidanan. Penelitian ini menggunakan metode analitik bagian silang dengan menggunakan sampel random bertingkat, dilakukan pada April-Mei 2013 terhadap 92 wanita hamil dan ibu bayi/balita (dibawah lima tahun) yang berpartisipasi dalam konseling dan pemeriksaan kesehatan oleh mahasiswa dalam praktik kebidanan komunitas. Variabel tentang kualitas praktek mahasiswa dan manfaat praktek diukur dengan menggunakan kuesioner. Uji statistik yang digunakan adalah uji Pearson, Tes Regresi Linier Pelbagai, dan faktor yang paling berpengaruh dianalisis dengan menggunakan analisis jalur. Hasil penelitian menunjukkan bahwa kualitas praktek mahasiswa berkaitan dengan keberhasilan mahasiswa dalam praktek kebidanan komunitas (r = 0.616, p < 0.001). Dimensi yang paling berpengaruh dari kualitas itu yakni empati, jaminan, dan usia subjek sebagai variabel penyela (p value < 0.001); dan efek gabungan semuanya adalah 33.7% (p < 0.001). Akhirnya, kualitas praktek mahasiswa terkait dengan sukses praktek kebidanan komunitas, dimensi yang paling berpengaruh adalah empati dan jaminan.KATA KUNCI: Kualitas, pelayanan, masyarakat, bidan, praktek, ketidakpuasan, mahasiswa, konseling dan pemeriksaan kesehatan, empati, dan jaminan.About the Author: Fuadah Ashri Nurfurqoni is Graduate Student, Alumnus Master of Midwifery UNPAD (Padjadjaran University) Bandung, Jalan Raya Bandung-Sumedang, UNPAD Campus, Jatinangor, Sumedang, West Java, Indonesia. Corresponding author is: ashrihenry05@yahoo.comHow to cite this article? Nurfurqoni, Fuadah Ashri. (2014). âRelationship between Quality of Student Practice and Success of Community Midwifery Practiceâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7, No.1 [Mei], pp.107-114. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of article: Accepted (March 17, 2014); Revised (April 20, 2014); and Published (May 20, 2014). Â  Â